2015
DOI: 10.1073/pnas.1506488112
|View full text |Cite
|
Sign up to set email alerts
|

Progressive maturation of silent synapses governs the duration of a critical period

Abstract: During critical periods, all cortical neural circuits are refined to optimize their functional properties. The prevailing notion is that the balance between excitation and inhibition determines the onset and closure of critical periods. In contrast, we show that maturation of silent glutamatergic synapses onto principal neurons was sufficient to govern the duration of the critical period for ocular dominance plasticity in the visual cortex of mice. Specifically, postsynaptic density protein-95 (PSD-95) was abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
172
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(193 citation statements)
references
References 74 publications
(120 reference statements)
16
172
0
2
Order By: Relevance
“…Notably, no changes in GABAergic or NMDA receptor currents are observed, suggesting that the reactivation of plasticity by PSD-95 deletion lies downstream of the regulation of inhibitory circuitry. A conversion of ‘silent’ to functional synapses has been proposed as a general mechanism to constrain plasticity across brain regions (Greifzu et al, 2014; Huang et al, 2015). …”
Section: Molecular Reactivation Of Critical Period In Adulthoodmentioning
confidence: 99%
“…Notably, no changes in GABAergic or NMDA receptor currents are observed, suggesting that the reactivation of plasticity by PSD-95 deletion lies downstream of the regulation of inhibitory circuitry. A conversion of ‘silent’ to functional synapses has been proposed as a general mechanism to constrain plasticity across brain regions (Greifzu et al, 2014; Huang et al, 2015). …”
Section: Molecular Reactivation Of Critical Period In Adulthoodmentioning
confidence: 99%
“…Accordingly, PSD-95 KO mice exhibit lifelong ODP (Huang et al, 2015). Interestingly, defects of PV + INs disrupting CP mechanisms were found in V1 of MeCP2 null mice (Krishnan et al, 2015), and conditional deletion of MeCP2 in PV + cells completely abolished CP plasticity (He et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Because these modifications are assumed to underlie the development of amblyopia, excitatory synapses represent strong candidate targets for its treatment. Indeed, recent reports have revealed that changes in the levels of the excitatory postsynaptic density protein PSD-95 govern the duration of the critical period for ocular dominance (OD) plasticity in the visual cortex, independent of changes in inhibitory circuits (Huang et al, 2015). PSD-95 expression increases in the visual cortex during the critical period for OD plasticity and promotes the progressive maturation of the so-called “silent” synapses that contain only NMDA-type glutamate receptors and that lack AMPA receptors.…”
Section: New Molecular/pharmacological and Genetic Approachesmentioning
confidence: 99%
“…Genetic loss of PSD-95 function leads to the persistence of silent synapses, allowing the juvenile form of OD plasticity to be maintained lifelong. Strikingly, using a viral gene silencing approach to reduce PSD-95 in the visual cortex of adult mice rejuvenates excitatory synapses by reinstating silent synapses like those in the immature cortex and reopens a critical period for visual cortical plasticity (Huang et al, 2015). …”
Section: New Molecular/pharmacological and Genetic Approachesmentioning
confidence: 99%
See 1 more Smart Citation